Quality of Romantic Relationships and Mortality Salience Predict Parenthood vs. Career-Oriented Intentions: A Terror Management Perspective - Contu, Federico; Ambrosio, Alessandra; Pantaleo, Giuseppe; Sciara, Simona (Psychology Hub, 2023)
Drawing on Terror Management Theory (TMT; Greenberg et al., 1986; for reviews: Arrowood and Cox, 2020; Pyszczynski et al., 2015), this study examined how people living in a high-quality romantic relationship would react to reminders of their own mortality and increase their desire for offspring. Two hundred and twenty undergraduate students engaged in romantic relationships were first asked about the quality of their relationship, and then randomly assigned to one of two experimental conditions (mortality salience vs. dental pain). After completion of a filler task intended to activate distal terror management defenses, participants were asked about their desire for children, ideal time-lapse before having children, and relevance of professional vs. family goals (dependent variables). Results showed that participants in high-quality relationships, if compared with their counterparts involved in low-quality relationships, when reminded of their mortality, manifested a stronger desire for children, were less intentioned to postpone parenting, and were also less ready to prioritize their professional career over having children. The above results suggest that people in high-quality relationships—i.e., people involved in secure, harmonious, and stable relationships—may rely on comparatively stronger intentions concerning parenthood as pertinent terror management defenses as a way of coping with their existential anxieties.